Neonatal myocardial infarction: A retrospective study and literature review. (December 2019) - Aljohani, Othman A.; Perry, James C.; El-Sabrout, Hannah R.; Hegde, Sanjeet R.; Silva Sepulveda, Jose A.; Catanzarite, Val A.; Tarsa, Maryam; Kimball, Amy; Moore, John W.; El-Said, Howaida G.
Abstract: Neonatal myocardial infarction (MI), in the absence of congenital heart disease or cardiac surgery involving the coronaries, is a rare condition with associated high mortality. A cluster of neonatal myocardial infarction cases was observed, leading to an investigation of causes and contributors. We performed a single-center review of neonates >37 weeks between 2011 and 2017 to identify neonates with myocardial infarction. Neonates with prior cardiac surgery, congenital anomalies of the coronaries, or sepsis were excluded. Diagnosis of MI was based on ECG changes, elevated troponin, decreased function or regional wall abnormality, and abnormal coronary angiography. There were 4, 583 admissions to the NICU without interval changes in referrals or the incidence of neonatal asphyxia. There were six cases of neonatal myocardial infarction. Of 2, 155 admissions in the first three years, there were no cases. The incidence in the next three years was 1.3/1, 000, 2.7/1, 000, and 3.3/1, 000. There was a significant difference (0.03, Fishers exact) between the first and second halves of the study period. All cases underwent catheterization, revealing coronary artery thrombosis requiring thrombolytic therapy. Additionally, obstetric providers were surveyed to determine changes in umbilical cord handling practices. Of 48 obstetric providers, 57% changed their practice of cord clamping since 2014: 13% reported cord milking then clamping; 47% delayed cord clamping for a few minutes; 28% delayed cord clamping until the cord stopped pulsating; and 13% immediate clamping. Only 40% reported routine documentation of cord clamping. In conclusion, there was an increased incidence of neonatal myocardial infarction due to coronary thrombosis. Early diagnosis and initiation of therapy of neonates with myocardial infarction can improve outcomes. A larger study cohort could lead to better understanding of risk factors and outcomes of myocardial infraction in neonates. Highlights: A high index of suspicion is needed to diagnose a neonate with myocardial infarction(MI). In neonatal MI, ECG can show nonspecific findings. Early reestablishment of coronary blood flow is a key for myocardial recovery in neonates with MI. Coronary angiography can show a subtle occlusion with a strand of thrombus. A thrombosis expert is needed for hypercoagulable workup interpretation in neonates.